Profiling antimalarial drug-resistant haplotypes in , 1, and genes in causing malaria in the Central Region of Ghana: a multicentre cross-sectional study - Mavis Puopelle Dakorah; Enoch Aninagyei; Juliana Attoh; Godwin Adzakpah; Isaac Tukwarlba; Desmond Omane Acheampong (Therapeutic Advances in Infectious Disease)
Background: The proliferation of Plasmodium parasites resistant to antimalarial drugs poses a serious threat to human life and remains an obstacle to managing and eradicating Plasmodium falciparum . The surveillance of molecular markers has become necessary to monitor the spread of resistant haplotypes and discover emerging mutations. Objective: This molecular epidemiological study aimed to evaluate the prevalence of known mutations in the drug resistance genes Pfcrt , Pfmdr 1, Pfdhfr and Pfdhps in the Central Region of Ghana. Design: A multi-centre cross-sectional study. Methods: This prospective study utilised dried blood spots from individuals with P. falciparum-infection from five districts in the Central Region of Ghana. Selective Whole Genome Amplification (sWGA) and Single Nucleotide Polymorphisms (SNPs) in P. falciparum chloroquine transporter genes ( Pfcrt ), P. falciparum multidrug resistance 1 ( Pfmdr 1), P. falciparum dihydropteroate synthase ( Pfdhps ) and P. falciparum dihydrofolate reductase ( Pfdhfr ) were analysed. Results: Whole genome sequencing was carried out on 522 samples. Of these, 409 (78%) samples were successfully sequenced. Six (6) of the sequenced samples were of co-infection of other parasite species with P. falciparum and excluded from the analysis. Analysis of the Pfcrt gene revealed 0.5% were CVIET (C72, V73, M74I, N75E, K76T) while the Pfcrt CVMNK (C72, V73, M74, N75, K76) wild-type haplotypes were 97% with (2.5%) (CV[M/I][N/E][K/T]) being mixed haplotypes. In the Pfmdr 1 gene, monoclonal haplotypes; NFD (N86, Y184F, D1246) and YFN (N86Y, Y184F, D1246N) occurred at 44% and 9.8%, respectively, whereas mixed- haplotypes (N[Y/F]D and [N/Y][Y/F]D) were 23.5% and 0.3%, respectively. Combined Pfdhfr / Pfdhps genes yielded about 88% Pfdhfr IRNI (N51I, C59R, S108N, I164) +  Pfdhps A437G haplotypes (conferring partial resistance to Sulphadoxine-Pyrimethamine (SP)) while 9% of the parasites had Pfhdfr IRNI +  Pfdhps A437G + K540E haplotypes (conferring full resistance to SP). The wild-type haplotype, Pfdhfr (N51, C59, S108, I164) and Pfdhps (S436, A437, K540, A581, A613) was not observed. Conclusion: The findings show a low prevalence of CVIET and relatively higher rates for Pfmdr 1 NFD and parasites with Pfdhfr IRNI (N51I, C59R, S108N, I164) +  Pfdhps A437G haplotypes. These observations advocate for enhanced surveillance which is inimical to malaria management in an endemic area.